The polymorphism L204F affects transport and membrane expression of the sodium-dependent organic anion transporter SOAT (SLC10A6). Issue 179 (May 2018) - Bakhaus, Katharina; Fietz, Daniela; Kliesch, Sabine; Weidner, Wolfgang; Bergmann, Martin; Geyer, Joachim
Highlights: The SOAT-L204F polymorphism showed reduced transport activity for DHEAS. SOAT-L204F showed impaired membrane expression. SOAT-L204F was found in subjects with normal spermatogenesis and with hypospermatogenesis. SOAT-L204F seems not to be causative for hypospermatogenesis per se. Abstract: Sodium-dependent organic anion transporter (SOAT) represents a membrane transporter specific for sulfated steroid hormones, which are supposed to participate in the regulation of reproductive processes. In man, SOAT shows predominant mRNA expression in the testis and here was localized to primary spermatocytes. SOAT mRNA expression is significantly downregulated in different disorders of spermatogenesis, including hypospermatogenesis. The resulting decline of SOAT-mediated transport of sulfated steroids may participate in the impairment of functional spermatogenesis. Apart from downregulation of SOAT mRNA expression, genetic polymorphisms affecting the transport function of SOAT may have the same negative effect on spermatogenesis. Therefore, in the present study we searched for functionally relevant SOAT polymorphisms, aiming to comparatively analyze their occurrence in patients with impaired spermatogenesis vs. patients with intact spermatogenesis. We found that the SOAT polymorphism L204F showed a significantly reduced transport function for DHEAS when expressed in HEK293 cells. Although the Km value was identical with that of the SOAT wildtype, the Vmax value dramatically declined for the SOAT-L204F variant (942.5 vs. 313.6 pmol × mg protein −1  × min −1 ). Although the same amount of total SOAT-L204F protein was detected in transfected HEK293 cells compared to the SOAT wildtype, plasma membrane expression was significantly reduced, which points to a plasma membrane sorting defect of the SOAT-L204F variant. Groups of 20 subjects with normal spermatogenesis and 26 subjects with hypospermatogenesis were genotyped for this polymorphism. Both groups showed nearly identical distributions of the SOAT-L204F polymorphism (∼10% heterozygous and ∼5% homozygous), indicating that this polymorphism seems not be causative for hypospermatogenesis.